Multi-response optimisation of the deep cryogenic treatment for 21-4N valve steel. (1st January 2011) - Jaswin, M. Arockia; Lal, D. Mohan
This paper deals with the optimisation of the deep cryogenic treatment process for 21-4N valve steel to maximise the tensile strength, hardness and wear resistance using Grey-Taguchi method. The factors considered for the optimisation are the cooling rate, soaking temperature, soaking period and aging temperature, each at three different levels. Nine experimental trials based on the L9 (3 4 ) orthogonal array were conducted. The analysis of variance (ANOVA) is performed to identify the significant contribution of parameters. A confirmation test is conducted to validate the test result. The improvement in tensile strength, hardness and wear resistance from the untreated samples to the deep-cryo treated samples at the optimised treatment condition are 11.87%, 15.32% and 27.8% respectively. The result of the confirmation experiment shows that the responses are improved simultaneously through the optimal combination of the deep cryogenic treatment parameters obtained from the proposed method.